Is Lateropulsion Really Related with a Specific Lesion of the Brain? - Lee, Kyoung Bo (Brain Sci, 2021)
Lateropulsion (pusher syndrome) is an important barrier to standing and gait after stroke. Although several studies have attempted to elucidate the relationship between brain lesions and lateropulsion, the effects of specific brain lesions on the development of lateropulsion remain unclear. Thus, the present study investigated the effects of stroke lesion location and size on lateropulsion in right hemisphere stroke patients. The present retrospective cross-sectional observational study assessed 50 right hemisphere stroke patients. Lateropulsion was diagnosed and evaluated using the Scale for Contraversive Pushing (SCP). Voxel-based lesion symptom mapping (VLSM) analysis with 3T-MRI was used to identify the culprit lesion for SCP. We also performed VLSM controlling for lesion volume as a nuisance covariate, in a multivariate model that also controlled for other factors contributing to pusher behavior. VLSM, combined with statistical non-parametric mapping (SnPM), identified the specific region with SCP. Lesion size was associated with lateropulsion. The precentral gyrus, postcentral gyrus, inferior frontal gyrus, insula and subgyral parietal lobe of the right hemisphere seemed to be associated with the lateropulsion; however, after adjusting for lesion volume as a nuisance covariate, no lesion areas were associated with the SCP scores. The size of the right hemisphere lesion was the only factor most strongly associated with lateropulsion in patients with stroke. These results may be useful for planning rehabilitation strategies of restoring vertical posture and understanding the pathophysiology of lateropulsion in stroke patients.